Web 2.0 Tools and Educational Usage Self-Efficacy: A Scale Development Study - AYDEMİR, ZEYNEP (ELSEVIER SCIENCE BV, 2014)
The purpose of this study is to develop a valid and reliable scale for Web 2.0 Tools and Educational Usage Self-Efficacy. The experts were consulted for content validity. However a factor analysis was held for structure validity. The considering the 57-item scale in total, the scale was found to have an eight-factor structure. The factor loading of 57 items changes between 0.62 and 0.88. The eight factors of the scale explain 76.09% of the total variance. To examine the reliability of the scale, internal consistency coherence is calculated. The internal consistency of the 57-item Web 2.0 Tools Self-Efficacy Belief Scale was 0.97. These values show that the scale is reliable and it validates. (C) 2013 The Authors. Published by Elsevier Ltd.
Keywords: Web 2.0 Tools; Educational Usage; Self-efficacy; Introduction